Highly stereoselective approach toward the synthesis of the macrolactone core of amphidinolide W - Mohapatra, Debendra K.; Chatterjee, Bhaskar; Gurjar, Mukund K. (Tetrahedron Letters, 2009)
The diastereoselective synthesis of the macrolactone core of amphidinolide W was successfully accomplished using Evans' asymmetric alkylation, Aldol reaction, Julia-Kocienski olefination, and Kita's macrocyclization protocol. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Amphidinolide W; Evans aldol; Evans alkylation; Julia-Kocienski olefination; Kita's macrocyclization